A Chinese Nurse’s Socio-Cultural Experiences in Australia - Huang, Yang (Journal of International Students, 2014)
Studying overseas for international students means a lot–not only being away from home but also experiencing quite a few unexpected difficulties. It looks like a triangle of a pyramid since each part is closely connected with each other, and it falls apart if one part is not functioning! Studying abroad is full of challenges for every student due to the language barrier, culture shock and homesickness. For students who speak English as a second or foreign language, this is because being disconnected with families, friends, familiar environment and even preferred food may lead to directly or indirectly physical discomfort and emotional stress. I chose overseas studying as I was eager to understand the cultural differences, linguistic variables, and to establish my interest in community and medicine!